Pola dan struktur pertumbuhan ekonomi serta ketimpangan pembangunan antar daerah di Provinsi Jambi - Syafrial Syafrial; Amri Amir (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze the pattern and structure of economic growth and development inequality between regions in Jambi Province. The data used are secondary data for the period 2004 - 2013 sourced from the Jambi Provincial Statistics Office and Jambi Province BAPPEDA. Data were analyzed descriptively using the Klassen Typology, Williamson Index and Theil Entropy Index. The results of the study found that there was no shift in the pattern and structure of economic growth in Jambi province. The economic growth of Jambi Province is relatively fluctuating with a tendency to increase. Inequality in economic development in Jambi Province in the period 2004 to 2013 was categorized as low.